Are there car seats in Qatar? Results and recommendations from a rapid market survey - Shahnaz Malik (19774584) (2015)
Mortality for young children in motor vehicle crashes in Qatar was highest in those who were unrestrained1. Anecdotal reports have attributed low car seat use to their expense and unavailability prompting car seat giveaway programs, but an assessment of the local car seat market has not been conducted previously. This study will report the results of a rapid market survey (RMS) to understand the availability, characteristics and the cost of child restraints and make recommendations for future child restraint policies and legislation in Qatar. This RMS was conducted as part of the Young Kids in Safe Seats Project funded by the Qatar Foundation. The survey involved locating all retail outlets that sell child restraints in Qatar and collecting standard data on each restraint system: brand, model no. age/weight limits, compliance with standards, availability and language of owner's manual. The RMS showed a sufficient number and variety of car seat models [83] available at 19 retail outlets with a wide affordability range [$46 - $810]. All of the car seats complied with the European standard. Only 2% showed a date of manufacture or expiry. A user manual was available in only 71% of seats and in a variety of different languages, but only 36% in the native language of Arabic. This RMS demonstrates the availability and variety of child restraint systems in Qatar. Unavailability and expense cannot be cited as barriers to their use and the market is prepared for legislation requiring car seats for children in Qatar. Areas for improvement include: requiring user manuals for all seats, especially in Arabic, that all car seats comply with globally accepted safety standards, especially expiry/manufacturing dates, given the harsh local climate, and encouraging more variety in the local markets. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.41